Analysis of Antioxidant Capacity of Chromones in Saposhnikoviae Radix Obtained by Ultrasonic-Assisted Deep Eutectic Solvents Extraction - Xianwen Yue; Fangfei Xu; Peng Lv; Huailei Yang; Huiwei Bao; Yang Xu (Journal of Analytical Methods in Chemistry)
In this paper, ultrasonic-assisted deep eutectic solvent (DES) extraction was applied to the acquisition of chromones (cimicifugin, prim-o-glucosylcimifugin, and 5-o-methylvisamminoside) from Saposhnikoviae radix (SR). The extraction effects of 11 prepared DESs were screened taking contents of chromones as indexes. Furthermore, the optimum extraction conditions were confirmed using a single-factor test and response surface optimization test. Scavenging activities of DPPH anion and ABTS cation radicals of different SR extracts (DES, methanol, and ethanol) were studied. The analysis results of best extraction conditions optimized by Design-Expert software were as follows: extraction time (40 min), extraction temperature (60°C), and the solid/liquid ratio (32 mL/g). Scavenging rates of the DES extract for DPPH anion radical and ABTS cation radical were found to be 75.31% and 65.71%, which were higher than those of methanol and ethanol extracts. In conclusion, the developed extraction method can be regarded as a safe, green, and more effective approach for the extraction of chromones in SR.